Task vs. Relationship-Oriented Leadership: Measuring Organizational Performance in Small, Medium and Micro Enterprises (SMMEs) in Johannesburg, South Africa - Pillay, Leevashen; Boodhoo, Suvera; Chuchu, Tinashe (Management Analysis Journal, 2026)
This study examines the influence of task-oriented and relationship-oriented leadership styles on organisational performance in small, medium, and micro enterprises (SMMEs) in Johannesburg, South Africa. The novelty of the study lies in simultaneously analysing autocratic, transactional, and transformational leadership styles within the underexplored context of South African SMMEs. Data were collected from 194 SMME owners and managers using a structured survey and analysed through structural equation modelling (SEM) to test the hypothesised relationships between leadership styles and organisational performance. The findings reveal that autocratic, transactional, and transformational leadership styles all have significant positive effects on organisational performance. These results suggest that leadership effectiveness in SMMEs is not confined to a single dominant style but rather depends on the contextual application of different leadership approaches. The study provides practical insights for SMME leaders and policymakers by highlighting the importance of adapting leadership behaviours to the dynamic and resource-constrained environments typical of emerging economies. Overall, the research contributes to leadership and small business literature by demonstrating how leadership adaptability supports organisational performance and sustainability in SMMEs.